Peasant Agency and Local Orders in Post-Agreement Colombian Marginalised Regions (2023)
With the implementation of the Final Peace Agreement in Colombia, in particular with the Programas de Desarrollo con Enfoque Territorial (PDETs, Development Programmes with a Territorial Focus), Colombia has been characterised by the development of differentiated processes of state construction, configuration of the armed conflict and territorial transformations. However, from being one of the great promises of peace, the PDETs have become instead an element of conflict by not including community governance initiatives in their implementation, nor have they recognised the legacies of rebel governance in marginalised regions, as occurs in Argelia (Cauca) and in Pradera (Valle del Cauca), Colombia